Entrepreneurial Intention among IT Students Through Entrepreneurship Development Education: A Case Study of a Mahalaxmi Polytechnic Institution in Nepal - Thapa, Harish Singh; Gautam, Suresh; Poudel, Suman; Pokharel, Jeena (Journal of Technical Education and Training, 2025)
Entrepreneurship development education (EDE) promotes entrepreneurship and boosts economic growth and employment. The comprehensive educational effort aims to foster students’ entrepreneurial intentions. In Nepal, the Council for Technical Education and Vocational Training (CTEVT) has integrated the EDE course curriculum into all diploma programs in engineering, including the Diploma in Information Technology (DIT) program, with the aim of enhancing students’ entrepreneurial knowledge and skills. Based on this context, the objective of this study was to explore the experiences of final-year diploma in information technology students about their entrepreneurial intentions through an EDE course. The study employs a qualitative case study methodology to investigate the experiences of final-year DIT students. The study selected sixteen students, ten of whom were male and six of whom were female. Data collection involved conducting semi-structured face-to-face interviews and document analysis. The analysis of the students’ interviews and the document analysis yielded three major themes: entrepreneurial attitude, entrepreneurial behavior, and entrepreneurial knowledge, along with twelve subthemes. The current study’s findings were consistent with planned behavior theory, which acts as a moderator for DIT students’ entrepreneurial intentions. The results of this study conclude that EDE plays a crucial role in fostering entrepreneurial intentions among IT students. The program enhances their attitudes, behaviors, and knowledge of entrepreneurship; therefore, we recommended that CTEVT Nepal incorporate the EDE curriculum for all TVET programs.